Reproductive Biology of Bothrops erythromelas from the Brazilian Caatinga. (16th December 2014) - Alberto Barros, Verônica; Rojas, Claudio Augusto; Almeida-Santos, Selma Maria
Abstract : The reproductive biology of Bothrops erythromelas, a small pit viper from the Caatinga, a semiarid biome in Brazil, is described based on analysis of individuals deposited in zoological collections. Males are smaller and also attain sexual maturity at a smaller size than females. Female reproductive cycle is seasonal with an extended period of secondary vitellogenesis and births occurring in a restricted period from late spring to early summer. Sperm storage in females may probably occur in infundibular tubular glands and uterine muscular twisting (UMT), which is a polymorphic condition within B. erythromelas . Seasonal spermatogenesis in males is variable with some intraspecific variation regarding the male reproductive stage per season. Most males are reproductively active during spring/summer and reproductively quiescent during autumn/winter, although some individuals vary (e.g., show testicular spermatogenesis and active sexual segment of the kidneys (SSK) during winter). The SSK could be identified in every male. Most males showed highly hypertrophied SSK in spring/summer and moderately hypertrophied SSK in autumn/winter. The ampulla ductus deferentis was observed and histochemical reactions were conducted. We discuss the probable influence of the unique environmental conditions of the Caatinga region and phylogenetic inertia in the reproductive patterns of this snake species.